Collective stresses drive competition between monolayers of normal and Ras-transformed cells. Issue 4 (5th December 2018) - Moitrier, Sarah; Blanch-Mercader, Carles; Garcia, Simon; Sliogeryte, Kristina; Martin, Tobias; Camonis, Jacques; Marcq, Philippe; Silberzan, Pascal; Bonnet, Isabelle
Abstract : Ras-transformed HEK cell sheets displace normal HEK cell sheets due to larger collective stresses developed at the interface. Abstract : We study the competition for space between two cell lines that differ only in the expression of the Ras oncogene. The two cell populations are initially separated and set to migrate antagonistically towards an in-between stripe of free substrate. After contact, their interface moves towards the population of normal cells. We interpret the velocity and traction force data taken before and after contact thanks to a hydrodynamic description of collectively migrating cohesive cell sheets. The kinematics of cells, before and after contact, allows us to estimate the relative material parameters for both cell lines. As predicted by the model, the transformed cell population with larger collective stresses pushes the wild type cell population.